The Viral Interferon Regulatory Factors of KSHV: Immunosuppressors or Oncogenes? - Damania, Blossom; Jacobs, Sarah R. (Frontiers in Immunology, 2011)
Kaposi’s Sarcoma-Associated Herpesvirus (KSHV) is a large double stranded DNA gammaherpesvirus, and the etiological agent for three human malignancies: Kaposi’s sarcoma, primary effusion lymphoma, and multicentric Castlemen’s disease. To establish and maintain infection, KSHV has evolved unique mechanisms to evade the host immune response. Cellular Interferon Regulatory Factors (IRFs) are a critical part of the host anti-viral immune response. KSHV encodes four homologs of IRFs, vIRF1-4, which inhibit the activity of their cellular counterparts. vIRF1,2, and 3 have been shown to interact directly with cellular IRFs. Additionally, the vIRFs have other functions such as modulation of Myc, p53, Notch, TGF-beta, and NF-kappaB signaling. These activities of vIRFs may contribute to KSHV tumorigenesis. KSHV vIRF1 and vIRF3 have been implicated as oncogenes, making the understanding of KSHV vIRF function vital to understanding KSHV pathogenesis.